Emotional Regulation in Only Children : Understanding Behavioral Patterns, Parental Influence, and Social Adaptation - Nusi Nisa Desinta; Zahro Varisna Rohmadani; Andhita Dyorita Khoiryasdien (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Emotional regulation includes efforts to accept emotions, control impulsive behavior, and the ability to use emotional regulation strategies appropriately and flexibly according to situational demands. It plays a significant role in maintaining mental well-being and fostering healthy interpersonal relationships. This study aims to explore and describe the emotional regulation strategies employed by only children, given the unique familial and social environment in which they are raised. The subjects in this study were three only children aged between 15 and 21 years, selected using purposive sampling techniques. The research employed a qualitative method with a phenomenological approach to gain a deep un-derstanding of their emotional experiences and regulation strategies. Data were collected through in-depth interviews and analyzed thematically. The findings revealed that all three subjects were gen-erally able to regulate their emotions effectively. They demonstrated self-awareness of their emotional states and employed various coping strategies, such as engaging in enjoyable activities like listening to music, exercising, journaling, or spending time in nature. In moments of emotional distress, they tended to seek social interaction rather than withdrawing or isolating themselves. This proactive engagement helped them maintain emotional balance and gain support from their social environment. Additionally, the subjects showed an ability to reflect on their feelings and manage impulsive reactions in challenging situations. Family support, particularly from parents, was found to play a crucial role in shaping their emotional coping mechanisms. The study concludes that only children, despite not having siblings, are capable of developing healthy emotional regulation skills through supportive environments and adap-tive personal strategies.